Gender empowerment and parity in East Africa: evidence from climate-smart agriculture in Ethiopia and Kenya - Tesfaye, Abonesh; Radeny, Maren A.O.; Ogada, Maurice Juma; Recha, John W.M.; Ambaw, Gebermedihin; Chanana, Nitya; Huyer, Sophia; Demeke, Getamesay; Solomon, Dawit (Informa UK Limited, 2023)
The aim of this study is to understand the role of climate-smart villages (CSVs) in promoting genderempowerment and equality in East Africa. This paper uses data collected from 280 and 305 randomlyselected farm household heads in Doyogena (Ethiopia) and Nyando (Kenya), respectively. To analysethe data, the gender empowerment index for climate resilient agriculture (GEI-CRA) and the genderparity index (GPI) were constructed based on guidelines from the literature. In both Doyogena andNyando, households in CSVs scored higher GEI. Comparing men and women in the CSVs, womenwere found to be more empowered compared to men and comparing between the two sites,household heads in Doyogena were more empowered than those in Nyando. Regarding gender parityindex (GPI), in both sites, majority of the women in the empowered households in CSVs were either atequal status with men or even at higher status than men. Thesefindings shed light on the potentialof CSVs in enhancing gender empowerment and promoting gender equality. The positivecontribution of CSVs may guide policymakers to scale up these practices with a better-targetedapproach that recognize and adequately address the implementation of CSA practices so that menand women can equally benefit.